Detection of avian influenza virus H5N1 subtype in organs of chicken affected by higly pathogenic avian infuenza in East and West Java by using immunohistochemical technique - Damayanti, R; Dharmayanti, N.L.P.I; Indriani, R; Wiyono, A; ., Darminto (Indonesian Animal Sciences Society, 2004)
The study was conducted to detect antigen H5N1 of highly pathogenic Avian Influenza (HPAI) virus in various farms in East and West Java. The immunohistochemical technique was applied due to Hematoxilin-eosin (H&E) staining was impossible to visualize the antigen in tissue. Immunohistochemical staining was applied for some visceral organs collected from the areas where the outbreaks occurred in September-October 2003. The specimens were processed as histopathological paraffin blocks using standard method. The blocks that were suspected to have antigen H5N1 were cut and rabbit antisera to H5N1 produced from the local isolate was applied as the primary antibody. Biotinylated secondary antibody and avidin biotin peroxidase from a commercial kit were administered. The antigen present in the tissues were visualized by adding a substrate called Amino Ethyl Carbazole (AEC) resulting in reddish brown colour. This immunostaining proved to be accurate and reliably quick method to detect H5N1 antigen present in the avian tissues. In conclusion, the outbreak of bird flu was caused by H5N1 strain and the antigen could be found in wattles, combs, brain, trachea, lungs, heart, proventriculus, liver, spleen, kidney and ovary. Â Key words: Highly pathogenic Avian Influenza (HPAI), chicken, H5N1, outbreak, immunohistochemistry